2021
DOI: 10.17829/turcom.859299
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of News about Pandemic on Borsa Istanbul during the COVID-19 Financial Turmoil

Abstract: The COVID-19 pandemic, which emerged in December 2019 and then spread worldwide, has affected not only economic and social life but also the financial markets. It has left investors greatly panicked and affected their decisions. In this study, the effect of COVID-19 related news on Borsa Istanbul is analyzed using the panel quantile regression method. The study period is set between 10 March 2020 and 17 April 2020. The panic index, media hype index, fake news index, country sentiment index, infodemic index, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…The greater the index value of the media frenzy regarding the COVID-19 issue, the more the Sharia stock index is corrected (down). This study supports previous studies from Tan (2021a;2021b) and Zargar and Kumar (2021), who found that the Media Hype Index on COVID-19 significantly negatively affected returns and stock prices both individually and collectively in the stock market. Conversely, this study presents contrasting findings to those of Rakshit and Neog (2021), who concluded that media frenzy about an incident positively affects stock market performance.…”
Section: Discussionsupporting
confidence: 91%
“…The greater the index value of the media frenzy regarding the COVID-19 issue, the more the Sharia stock index is corrected (down). This study supports previous studies from Tan (2021a;2021b) and Zargar and Kumar (2021), who found that the Media Hype Index on COVID-19 significantly negatively affected returns and stock prices both individually and collectively in the stock market. Conversely, this study presents contrasting findings to those of Rakshit and Neog (2021), who concluded that media frenzy about an incident positively affects stock market performance.…”
Section: Discussionsupporting
confidence: 91%
“…The proxy variables that capture news arrivals and sentiment about them are obtained from the RavenPack New Analytics database; specifically, the news relevance score (REL), composite sentiment score (CSS), event sentiment score (ESS), and event novelty score (ENS) are used. Tan (2021) shows a similar asymmetric structure of dependence between the returns of Borsa Istanbul and pandemic news finding that the effect of COVID-19-related information varies amongst the quantiles. Umar et al (2021) studied the impact of the COVID-19-related Media Coverage Index on the dynamic return and volatility connectedness of the most important cryptocurrencies and the fiat currencies of the euro, GBP, and Chinese yuan from January 2020 to December 2020.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Data were extracted at a daily frequency starting on January 17, 2020, the first date for which pandemic anxiety indexes were available, and ending on February 16, 2022, prior to the collapse of the Russian stock market following the invasion of Ukraine. Regarding the fear in the market and uncertainty, and following several recent studies on the pandemic ( Baig et al, 2021 , Cepoi, 2020 , Haroon and Rizvi, 2020a , Tan, 2021 , Umar and Gubareva, 2020 , Umar et al, 2021 ), we measured the level of relationship between stock market returns of G7 countries and BRICS and the fear created by COVID-19. For this purpose, RavenPack’ Infodemic, Media Coverage and Media Hype indexes were used for each country as proxies for pandemic anxiety.…”
Section: Discussionmentioning
confidence: 99%